Car wash service in Nigerian's road transport system: evidence from Ilorin (2007)
The informal sector is a vital segment of the economy of most developing countries, including Nigeria. Research on the urban informal sector in general and the road transport sector in particular in Nigeria has neglected road transport supportive services. These services are crucial to the effective and efficient operation of the road transport system. This paper therefore examines one of such services, the car wash service, and uses Ilorin as the case study. The survey revealed that it is a sole proprietorship business dominated by males. About 95 per cent of the operators used informal financial sources, to start the business. It provides employment and income to operators who are mostly unskilled and have little formal education. The number of vehicles washed and the age of the business were found to be positive determinants of earnings, while apprentice access was found to impact negatively on earnings. The major constraints in the industry are irregular water supply and lack of financial assistance for development and modernization. For the full potential of this informal business activity to be realized, the water board needs to guarantee adequate supply of water, while the formal financial institutions should make the provision of finance easier to enable the car wash operators to modernize their operations.